Spirituality and Counselling: Are Counsellors Prepared to Integrate Religion and Spirituality into Therapeutic Work with Clients? - Plumb, Alison Marie (Canadian Journal of Counselling and Psychotherapy, 2011)
An online survey of 341 Registered Clinical Counsellors in British Columbia was used to understand how therapists view and integrate spirituality and religion in their practice. Therapists were asked about their education and training in this realm, and about their perceived abilities, comfort, and competence when working with religious and/or spiritual content. Results suggest that spirituality, but not necessarily religion, is important in participants’ lives and their work with clients, while fewer than half indicated that they were integrating spirituality into their practice. Discussion focuses on the need for practitioner comfort, confidence, and competence regarding spirituality in the therapeutic process.